2010
DOI: 10.31421/ijhs/16/5/926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water supply on canopy temperature, stomatal conductance and yield quantity of processing tomato (Lycopersicon esculentum Mill.)

Abstract: Tomato (Lycopersicon esculentum Mill.) is one of the most extensively cultivated horticultural crops in the world.Water supply is important for yield quantity and quality. The aims of the present study were 1) to evaluate the canopy temperature and the stomatal conductance on processing tomato substances with different water supply, 2) to investigate the effect of different water supply on yield quantity. There were two irrigated treatments, one of them was the reguralry irrigated plant stand which got 333 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…If soil water content is sufficient for the plant stand, the difference between canopy temperature and air temperature is zero or negative, but if the plants suffer from water stress this value is positive. An increase of 1 • C in canopy temperature related to a 10% decrease in the transpiration [31]. Size and stomatal density of genotypes are different thereby the transpiration varies in intensity which correlates with the difference of the canopy temperature of plants.…”
Section: Canopy Temperature-transpirationmentioning
confidence: 97%
See 4 more Smart Citations
“…If soil water content is sufficient for the plant stand, the difference between canopy temperature and air temperature is zero or negative, but if the plants suffer from water stress this value is positive. An increase of 1 • C in canopy temperature related to a 10% decrease in the transpiration [31]. Size and stomatal density of genotypes are different thereby the transpiration varies in intensity which correlates with the difference of the canopy temperature of plants.…”
Section: Canopy Temperature-transpirationmentioning
confidence: 97%
“…Helyes et al [31] found a close correlation between the stress degree days (SDD) and yield of tomatoes. If the canopy temperature exceeded the air temperature (at noon), transpiration was reduced, which indicated water stress and resulted in yield reduction and quantity.…”
Section: Relationship Between Drought Stress Markers and Yieldmentioning
confidence: 99%
See 3 more Smart Citations